(3JdNjU CYeGd GdMSGHs - (3CHi GdYHGS CMeO Hf eMeO YKeGf GdCROi GdeYQha HGHf GdHfGA GdeQGcTis
(3ChdgG (B:s
(3GdZQV ef gPG GdcJGH(B: (3JdNjU CYeGd GdMSGH hJbQjH CHhGHg heYGfjg hVHW bhGYOg heHGfjg , hgh jTJed Ydi LRFjf s
(3BNQgG (B:s
(3MeOfG eMOhO Bf ehLhO QG TcQfG eYOhO Bf eYHhO QG s
(3ai BNQgG efXheI HGddZI GdaGQSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B363 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B37 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B472s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3QjGVjGJ (B16) s
Keywords: (3GdQjGVjGJs